Methodological Approaches to Development Strategies for the Tourism and Hospitality Industry Enterprises - Evgenievna Konovalova, Elena; Vladimirovna Yudina, Elena; Viktorovna Uhina, Tatiana; Mikhailovich Lagusev, Yuri; Pavlovna Zvyagintseva, Olga (International Journal of Engineering and Technology, 2018)
The article is concerned with methodological approaches to development strategies for tourism and hospitality industry enterprises. It has been found that most regions, local tourist destinations, tourism and hospitality industry businesses do not have any clear formalized strategy. It was determined that some tourism and hospitality industry businesses apply only individual elements of strategic management, i.e. do not have an integrated system of strategic management. Methodological tools have been proposed for elaborating development strategies for tourism and hospitality industry enterprises, which show that strategic management, which is methodological by nature, i.e. is characterized by the conceptual approach and panoramic vision, cannot give an exact and clear view of the tourism industry’s future. It was proved that strategic management cannot be limited to a set of universal and routine rules, procedures or schemes. It was defined that strategic management requires great efforts, time and resources to make the activity of tourism and hospitality industry businesses remarkable.